METODE DIALEKTIKA HEGEL DAN ANALISISNYA ATAS PARADIGMA HUKUM - Muhammad Zulfikar Nur Falah; Ari Bachtiar Firmansyah; Luqman Hakim (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This article talks about the analysis of Hegel's dialectical method on the law paradigm, which, as is well known, the problem with the development of legal science, has recently only been viewed from a certain point of view, so that it is not as detailed as possible to provide an open solution. On the factor of the law paradigm that has been used, the author then makes a special research object to be investigated using descriptive analysis methods obtained through library research, with relevant and reliable sources such as books, journals, theses, theses, dissertations, and so on. Before obtaining an understanding of the implications of this research, the author first describes the biography of Hegel, and his dialectical method. Implicitly, this is so reflective, because it is able to reveal and produce the truth behind the nature of knowledge contained in the field of philosophy or the historical reality of the law paradigm. The dialectical series consists of the postmodernism law paradigm, which is the "antithesis" of the modern law paradigm as "synthesis". This, in essence, is the result of a combination of the ancient Greek law paradigm as a "thesis" statement and a summary of an abstract universal concept as the starting point for the emergence of the law paradigm that was put forward in the medieval period. More precisely, the law paradigm in ancient Greece was a statement of "thesis", while in the Middle Ages, the law paradigm used was as a statement "antithesis" of the ancient Greek law paradigm.